ORGANIZING BUSINESS FORUMS WITH INTEGER LINEAR PROGRAMMING - Pessanha,José Francisco Moreira (2019)
ABSTRACT Business associations often promote forums between entrepreneurs. One strategy for establish contacts among participants is to organize them into small groups assigning them to tables so that participants in the same group can present their companies and projects. After an interval, a new round begins with new groups in order to establish new contacts. The repetition of this strategy allows each participant to expand his/her business network, but the repeated contacts between participants should be avoided. We present an Integer Linear Programming model that minimizes the repeated contacts when the participants are successively assigned to new groups. The model was implemented in R programming language and it has been applied to organize business forums. In order to illustrate the model application, this paper shows the results from a case study with 108 participants.